Probing conformational dynamics in single donor-acceptor synthetic molecules by means of photoinduced reversible electron transfer - Cotlet, Mircea (National Academy of Sciences, 2004)
We use single-molecule fluorescence lifetimes to probe dynamics of photoinduced reversible electron transfer occurring between triphenylamine (donor) and perylenediimide (acceptor) in single molecules of a polyphenylenic rigid dendrimer embedded in polystyrene. Here, reversible electron transfer in individual donor-acceptor molecules results in delayed fluorescence that is emitted with a high photon count rate. By monitoring fluorescence decay times on a photon-by-photon basis, we find fluctuations in both forward and reverse electron transfer spanning a broad time range, from milliseconds to seconds. Fluctuations are induced by conformational changes in the dendrimer structure as well by polystyrene chain reorientation. The conformational changes are related to changes in the dihedral angle of adjacent phenyl rings located in the dendritic branch near the donor transferring the charge, a torsional motion that results in millisecond fluctuations in the “through-bond” donor-acceptor electronic coupling. Polymer chain reorientation leads to changes in the local polarity experienced by the donors and to changes in the solvation of the charge-separated state. As a result, switching between different donor moieties within the same single molecule becomes possible and induces fluctuations in decay time on a time scale of seconds.